OPTIMASI SODIUM LAURIL SULFAT DAN NATRIUM CHLORIDA PADA SABUN CAIR EKSTRAK LIDAH BUAYA: SIMPLEX LATTICE DESIGN - I Gusti Ngurah Agung Windra Wartana Putra; Ni Made Maharianingsih Maharianingsih; I Gusti Rai Widowati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
This study aims to determine the concentration of SLS and NaCl which can produce the best formula of aloe vera extract liquid soap (Aloe vera L.). The method used in this study is the Simplex Lattice Design method. Eight formulas were made with different concentrations of SLS and NaCl, then the parameters of viscosity, specific gravity, foam resistance, and pH were determined. The data obtained was tested with one sample t-test to see the difference between the software's design expert predicted results from the optimization method and the results of laboratory tests. From the results of testing the 8th parameter of the formula, the formula that has the closest desire ability value to 1 was chosen as the optimum formula, namely at a concentration of 180 g of SLS and 65 g of NaCl. From this formula, a one sample t test was carried out between the software's predicted value and laboratory parameter values. The significant values ​​obtained for the parameters of viscosity, specific gravity, foam resistance and pH were 0.570; 0.245; 0.882; 0.069. which means there is no difference in parameter values ​​between the software and the laboratory. It can be concluded that the formula with a variation of SLS of 180 g and NaCl of 65 g is the best formula in the formulation of aloe vera extract liquid soap which produces values ​​that meet quality requirements such as viscosity of 3270 Cp, Specific Weight of 1.079 g/ml, foam resistance of 67%, and pH value 6.73.